Penerapan Model Pembelajaran Kooperatif Tipe STAD (Student Team Achievement Division) di SMP Negeri 4 Sungai Raya Kabupaten Kubu Raya - Siska, Siska; Okianna, Okianna; Wiyono, Hadi; Buwono, Sri; Hafizi, M Zainul (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to determine the application of the STAD (Student Team Achievement Division) type cooperative learning model at SMP Negeri 4 Sungai Raya, Kubu Raya Regency. This study uses a quasi-experimental quantitative experimental method. The research subjects were 74 people (37 students in grades VII, C and E). Multiple-choice objective tests in the form of pretest and posttest are used as data collection techniques, and observation guides are used as data collection tools. The hypothesis was tested by paired sample t-test, and Shapiro Wilk's normality test was used in the data analysis method. Empirical evidence shows that the STAD model has been effectively applied in an educational environment. The results of the analysis showed that before and after the test of the normality test of the experimental class. After that, a parametric hypothesis test was carried out, and the results of the paired sample t-test showed a significance level (asymbiotic growth) of the asymptotic sig of 0.000<0.05 for the type of 2-tailed cooperative learning type which represents the 2-tailed asymptotic sig cooperative learning model. The STAD model influences students' learning goals.